Rural Nursing in Africa: Acts of Mercy - Angela Smith Collins (Rural Nurse Organization; Binghamton University, 2008)
This summer provided a chance to go to Uganda to serve a community by providing screening and simple interventional care. Community service is not an unfamiliar experience of this acute care nurse because colleagues at The University of Alabama, church fellowship, and Greater Birmingham Nursing chapter are active in efforts to address healthcare disparity in the United States. However, this journey into international community needs engaged not only nursing expertise, but also misconceptions about global health needs. Working alongside nineteen colleagues was a moment to make a difference. Friends have asked "How were you changed by this time in another part of the world?" The following paragraphs are three stories that explain some of the paradigm shifts that occurred.